2022
DOI: 10.1038/s41467-022-31503-0
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the S=3/2 Kitaev honeycomb spin liquids

Abstract: The S=3/2 Kitaev honeycomb model (KHM) is a quantum spin liquid (QSL) state coupled to a static Z2 gauge field. Employing an SO(6) Majorana representation of spin3/2’s, we find an exact representation of the conserved plaquette fluxes in terms of static Z2 gauge fields akin to the S=1/2 KHM which enables us to treat the remaining interacting matter fermion sector in a parton mean-field theory. We uncover a ground-state phase diagram consisting of gapped and gapless QSLs. Our parton description is in quantitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The spin-3/2 Kitaev honeycomb model is unique among the spin-S Kitaev models due to a massive ground state quasidegeneracy that has hampered numerical and analytical studies [152,194]. In a recent work [152], the authors have used an SO(6) Majorana parton mean-field theory and showed that the anomalous features of S-3/2 Kitaev QSL can be understood in terms of an emergent low-energy Majorana flat band.…”
Section: Semiclassical Approach To the Spin-s Kitaev Honeycomb Model:...mentioning
confidence: 99%
See 1 more Smart Citation
“…The spin-3/2 Kitaev honeycomb model is unique among the spin-S Kitaev models due to a massive ground state quasidegeneracy that has hampered numerical and analytical studies [152,194]. In a recent work [152], the authors have used an SO(6) Majorana parton mean-field theory and showed that the anomalous features of S-3/2 Kitaev QSL can be understood in terms of an emergent low-energy Majorana flat band.…”
Section: Semiclassical Approach To the Spin-s Kitaev Honeycomb Model:...mentioning
confidence: 99%
“…The spin-3/2 Kitaev honeycomb model is unique among the spin-S Kitaev models due to a massive ground state quasidegeneracy that has hampered numerical and analytical studies [152,194]. In a recent work [152], the authors have used an SO(6) Majorana parton mean-field theory and showed that the anomalous features of S-3/2 Kitaev QSL can be understood in terms of an emergent low-energy Majorana flat band. Away from the isotropic limit, when the S = 3/2 Kitaev spin liquid is supplemented with single-ion anistoropy term, it generally displays a quadrupolar order with gapped or gapless Majorana excitations, features that were quantitatively confirmed by DMRG simulations [152].…”
Section: Semiclassical Approach To the Spin-s Kitaev Honeycomb Model:...mentioning
confidence: 99%
“…It also attracts tremendous attention due to the discovery of candidate materials [2][3][4][5]. More recently, the higher-spin generalizations of the Kitaev materials were proposed [6][7][8][9][10][11][12] and have triggered extensive analytical and numerical studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%